Petroleum derivatives and their role in the achieving of Algerian economic diversification - Belguerbouz, Mostafa; Benguetib, Ali (International journal of economic perspectives, 2025)
This research aims to highlight the role and importance of petroleum derivatives in achieving economic diversification in order to get out of economic dependency and avoid the resulting economic problems. Through our study and the examination of the role of petroleum derivatives in economic diversification, we concluded that these derivatives play a significant role in the diversification process, that Algeria neglects this aspect, and that its economic policy is based on oil revenues.